2008
DOI: 10.1246/cl.2008.908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High-silica CHA Zeolite from FAU Zeolite in the Presence of Benzyltrimethylammonium Hydroxide

Abstract: A highly crystalline and pure high-silica chabazite zeolite with a Si/Al ratio of ca. 17 was obtained by the hydrothermal conversion of FAU zeolite used as a crystalline Si/Al source in benzyltrimethylammonium hydroxide media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 10 publications
1
72
0
Order By: Relevance
“…The rotor was spun at 4 kHz for 13 C CP/MAS and 29 Si MAS NMR, and at 6 kHz for 27 Al MAS NMR. The spectra were acquired using 6.0 ms pulses, a 25 s recycle delay, and 1000 scans for 13 …”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotor was spun at 4 kHz for 13 C CP/MAS and 29 Si MAS NMR, and at 6 kHz for 27 Al MAS NMR. The spectra were acquired using 6.0 ms pulses, a 25 s recycle delay, and 1000 scans for 13 …”
Section: Characterizationmentioning
confidence: 99%
“…Recently, our group has also investigated the potential of interzeolite conversion, and succeeded in the synthesis of several types of zeolites such as *BEA, RUT, CHA, LEV, MTN, and OFF using FAU zeolite as the starting material in the presence of various OSDAs [11][12][13][14][15][16]. Among the zeolites synthesized, LEV zeolite, which belongs to the chabazite (CHA) zeolite group, has attracted considerable interest because of its structure with eight-membered ring pores (4.8 Â 3.6Å) and because it shows a shape specific selectivity for the conversion of methanol or ethanol into light olefins such as ethylene and propylene.…”
Section: Introductionmentioning
confidence: 99%
“…First, in order to investigate the potential of interzeolite conversion of n BEA type zeolites into RUT type zeolites, we attempted the hydrothermal conversion of n BEA type zeolites using TMAOH, BTMAOH, and choline hydroxide, which were previously reported to be effective for interzeolite conversion of FAU type zeolites [16][17][18][19][20][21]. The synthesis conditions and products obtained are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Kubota et al [14] and Ahedi et al [15] also succeeded in the interconversion of Al-n BEA and Ti-n BEA into Al-SSZ-31 and Ti-SSZ-24, respectively. Very recently, we also succeeded in synthesizing n BEA, CHA, MTN, LEV, OFF, and RUT type zeolites using FAU type zeolite as the starting zeolite in the presence of a variety of SDAs such as tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), benzyltrimethylammonium hydroxide (BTMAOH), and choline hydroxide [16][17][18][19][20][21]. In the hydrothermal conversion of FAU type zeolite, it was found that when SDA is also employed as an alkali source, the use of FAU type zeolite as a starting material shows the enhanced crystallization rate zeolite as compared to amorphous silica/alumina, which are usually used as starting materials for the conventional zeolite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As synthesized zeolite without or with cheaper SDA is more competitive in commercial field [11,12], a lots efforts have been applied to generating improved methods for the synthesis CHA-type zeolite by using a small amount of TMADA + or other unexpensive SDAs. Very recently, there are a few of papers published related with the synthesis of SSZ-13, in which benzyl trimethyl ammonium cation (BTMA + ) instead of a typical SDA [13,14]. We have tried many times to synthesis SSZ-13 only used BTMA + as SDA and result with an impure phase of CHA zeolite.…”
Section: Introductionmentioning
confidence: 99%